Toll-Like Receptors, Associated Biological Roles, and Signaling Networks in Non-Mammals - Nie, Li; Cai, Shi-Yu; Shao, Jian-Zhong; Chen, Jiong (Frontiers in Immunology, 2018)
The innate immune system is the first line of defense against pathogens, which is initiated by the recognition of pathogen-associated molecular patterns (PAMPs) and endogenous damage-associated molecular patterns (DAMPs) by pattern recognition receptors (PRRs). Among all the PRRs identified, the Toll-like receptors (TLRs) are the most ancient class, with the most extensive spectrum of pathogen recognition. Since the first discovery of Toll in Drosophila melanogaster, numerous TLRs have been identified across a wide range of invertebrate and vertebrate species. It seems that TLRs, the signaling pathways that they initiate, or related adaptor proteins are essentially conserved in a wide variety of organisms, from Porifera to mammals. Molecular structure analysis indicates that most TLR homologs share similar domain patterns and that some vital participants of TLR signaling co-evolved with TLRs themselves. However, functional specification and emergence of new signaling pathways, as well as adaptors, did occur during evolution. In addition, ambiguities and gaps in knowledge still exist regarding the TLR network, especially in lower organisms. Hence, a systematic review from the comparative angle regarding this tremendous signaling system and the scenario of evolutionary pattern across Animalia is needed. In the current review, we present overview and possible evolutionary patterns of TLRs in non-mammals, hoping that this will provide clues for further investigations in this field.